Unveiling the Mineral Composition: Potassium and Magnesium Levels in Musa Paradisiaca L. Varieties from Medan's Traditional Markets Using Atomic Absorption Spectrophotometry (Talenta Publisher, 2024)
Bananas are rich in nutrients, particularly vitamin C, starch, sugar, fiber, and serve as an affordable source of vitamins, minerals, and energy for the community. The mineral content in fresh bananas includes zinc, selenium, phosphorus, manganese, iron, copper, and calcium. Consuming bananas for magnesium intake is particularly important. A single fresh banana contains 27 mg of magnesium. This study was conducted in the laboratory of the Faculty of Pharmacy using the Atomic Absorption Spectrophotometry (AAS) method, which is relatively fast and capable of measuring metal concentrations at low and specific levels for each element without requiring separation. The analysis results of potassium and magnesium in Ambon Bananas, Banten Bananas, Barangan Bananas, Kepok Bananas, Lilin Bananas, Mas Bananas, Raja Bananas, and Horn Bananas showed potassium levels of (367.1354 ± 1.4227) mg/100g; (412.7505 ± 0.9358) mg/100g; (386.6516 ± 0.6478) mg/100g; (413.2283 ± 0.6933) mg/100g; (405.5700 ± 0.7744) mg/100g; (417.1851 ± 0.5417) mg/100g; (374.8651 ± 0.6505) mg/100g; and (340.4262 ± 0.7292) mg/100g, respectively. The magnesium levels were found to be (44.2010 ± 0.1073) mg/100g; (57.9526 ± 0.0986) mg/100g; (45.9309 ± 0.0907) mg/100g; (82.8869 ± 0.2170) mg/100g; (79.2840 ± 0.0987) mg/100g; (59.1938 ± 0.0792) mg/100g; (76.8133 ± 0.0939) mg/100g; and (55.1193 ± 0.0734) mg/100g, respectively. The high potassium and magnesium levels found in this quantitative analysis indicate that bananas are highly beneficial for individuals with hypertension. Keywords: Banana, Potassium, Magnesium, Atomic Absorption Spectrophotometry